Slow‐Release Formulation of Cowpea Mosaic Virus for In Situ Vaccine Delivery to Treat Ovarian Cancer. Issue 5 (21st February 2018) - Czapar, Anna E.; Tiu, Brylee David B.; Veliz, Frank A.; Pokorski, Jonathan K.; Steinmetz, Nicole F.
Abstract: The plant viral nanoparticle cowpea mosaic virus (CPMV) is shown to be an effective immunotherapy for ovarian cancer when administered as in situ vaccine weekly, directly into the intraperitoneal (IP) space in mice with disseminated tumors. While the antitumor efficacy is promising, the required frequency of administration may pose challenges for clinical implementation. To overcome this, a slow release formulation is developed. CPMV and polyamidoamine generation 4 dendrimer form aggregates (CPMV‐G4) based on electrostatic interactions and as a function of salt concentration, allowing for tailoring of aggregate size and release of CPMV. The antitumor efficacy of a single administration of CPMV‐G4 is compared to weekly administration of soluble CPMV in a mouse model of peritoneal ovarian cancer and found to be as effective at reducing disease burden as more frequent administrations of soluble CPMV; a single injection of soluble CPMV, does not significantly slow cancer development. The ability of CPMV‐G4 to control tumor growth following a single injection is likely due to the continued presence of CPMV in the IP space leading to prolonged immune stimulation. This enhanced retention of CPMV and its antitumor efficacy demonstrates the potential for viral–dendrimer hybrids to be used for delayed release applications. Abstract : Assemblies consisting of the plant viral nanoparticle, cowpea mosaic virus (CPMV), and dendrimer, polyamidoamine generation 4, function as a slow‐release formulation for in situ vaccination of mice with ovarian cancer. By increasing the retention of the CPMV immunotherapeutic, a single administration of this assembly in murine ovarian cancer has a similar anticancer effect as repeated dosing with soluble CPMV.